Perception, Knowledge, Usage, and Effects of Herbal Medicine among Outpatients in a Tertiary Care Hospital in Southeast Nigeria: A Cross-Sectional Study - Tochukwu C. Okoli; Promise U. Okereke; Otitodilichukwu J. Okoh; Arinze V. Okolo; Boniface O. Okofia; Chukwunonso P. Nnegbo; Chidubem P. Okpechukwu; Chukwuemeka V. Umeh; Anthony C. Okeke; Olalekan S. Tola; Emmanuel U. Nwobi; Cecil A. Okpuzor; et al. (International Journal of Medicine and Health Development, 2025)
Background: The use of herbal medicine (HM) is common worldwide. Although some HMs have promising potential and are used widely, many of them remain untested and their use also not monitored. Objectives: This study assesses the perception, usage, knowledge, and effects of HM among outpatients in a Nigerian tertiary hospital. Materials and Methods: This is a cross-sectional study of outpatients of a Nigerian tertiary hospital, carried out using a simple random sampling technique. Data were collected using a pretested interviewer-administered questionnaire majorly, and some were self-administered. Data were entered into the Statistical Package for Social Sciences version 26, and descriptive (univariate and bivariate) analysis was performed. Results: A total of 182 questionnaires out of 185 were returned. There were 62 males (34.1%) and 120 females (65.9%). The majority of respondents, 41.2% were within the age bracket (20–29) years. A large majority, 98.9% have knowledge of HM, and 72.5% have used HM previously. Majority, 73.4% of those who used it previously used it without specified dosing, and 64.8% used it for treatment purposes (malaria = 54.7%, typhoid = 35.9%, abdominal pain = 25.0%, sexual wellness = 21.1%, and infertility = 19.7%). A significant relationship exists between respondents and their family/friends as major influencers of their usage (P = 0.030). Minority, 38 (28.8%) of the respondents have ever had any adverse effects/reactions from usage of HM in their lifetime. The most common adverse effect experienced was diarrhea (24/38, 63.2%). Conclusion: The prevalence of HM use in the study population is high. Healthcare workers should regularly educate the patients on the safety concerns of HM. Government should institute regulation of HM, and quality control measures should be put in place.